2008
DOI: 10.1111/j.1478-4408.2008.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the dependence of colour values on yarn structure

Abstract: The colour values of knitted cotton fabrics made from single and plied ring and compact yarns were investigated before and after dyeing. The fabric samples were knitted under the same constructional properties and then dyed with direct and reactive dyes. It was found that fabrics with ring yarns had high lightness and low chroma and colour strength values compared with fabrics with compact yarns. Also colour strength and colour difference values of dyed fabrics were assessed after increasing abrasion cycles (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
2
9
0
Order By: Relevance
“…The greatest changes in both L* and K/S values were examined between the not abraded fabric and the fabric after 2500 abrasion cycles. There was a small decrease in K/S values while observing a small increase in L* values after 2500 cycles which was compatible with the literature findings [5], [6], [10]. As previously stated, at earlier stages of abrasion tests, the fabric surface smoothness increases due to the removal of protruding fibers, and that brings higher light reflectance, causing L* values to increase and K/S values to decrease.…”
Section: Effect Of Abrasion On Color Values Of Knitted Fabricssupporting
confidence: 91%
See 2 more Smart Citations
“…The greatest changes in both L* and K/S values were examined between the not abraded fabric and the fabric after 2500 abrasion cycles. There was a small decrease in K/S values while observing a small increase in L* values after 2500 cycles which was compatible with the literature findings [5], [6], [10]. As previously stated, at earlier stages of abrasion tests, the fabric surface smoothness increases due to the removal of protruding fibers, and that brings higher light reflectance, causing L* values to increase and K/S values to decrease.…”
Section: Effect Of Abrasion On Color Values Of Knitted Fabricssupporting
confidence: 91%
“…As previously stated, at earlier stages of abrasion tests, the fabric surface smoothness increases due to the removal of protruding fibers, and that brings higher light reflectance, causing L* values to increase and K/S values to decrease. At later stages of the test, the change is mostly due to internal abrasion of the fabric, and thus the change in both L* and K/S is limited, especially when reactive dyes which are strongly bonded to fibers are used for dyeing [2], [4], [10].…”
Section: Effect Of Abrasion On Color Values Of Knitted Fabricsmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the nuance of the finished product is influenced by all chemical or mechanical including the knitting operations. Many problems influence the color quality such as the fiber characteristics, the parameters of manufacture and the textile structure itself [12]. The color change is also influenced by some other additional factors such as temperature, friction, water and atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been reported to evaluate the effects of increased number of abrasion cycles on color values of knitted and woven fabrics made from different fiber materials such as cotton, wool, polyester, viscose and different yarn structures in different fabric construction parameters. 915 From the color results, it was observed that color values of fabrics after abrasion cycles are closely related with fiber type, and yarn and fabric constructional parameters.…”
Section: Introductionmentioning
confidence: 99%